Evaluation of the Effectiveness of Authentic Assessment on Students’ Attitudes - Sabtiawan, Sabtiawan; Yuanita, Leny; Rahayu, Yuni Sri (Universitas Negeri Surabaya, 2013)
This study aimed to evaluate the effectiveness of using the authentic assessment on students’ attitudes involving interest and enjoyment when they learned Atomic Absorption Spectroscopy Topic. Selected sample of this research was 37 students of chemistry who enrolled in the Spectroscopic Methods of Analysis Subject, Mathematics and Natural Sciences Faculty, The State University of Surabaya. This research was conducted by using case study research. The data were gained through two techniques, namely, observation and interview, and were analyzed using descriptive qualitative. The findings informed that the students showed positive feelings toward the topic after and during learning constructed by using authentic assessment dimensions with embedded cooperative learning syntax, especially student’s interest and enjoyment. They felt interested to the topic because of three reasons, that are, learning the theory through practice, discussion intensively, and activity like the real workplace. Moreover, they enjoyed during the learning because of four reasons also, that are, discussion without reluctance, no forcing all concept at once, synchronizing between theory and practice occurring well, and learning in a team. In conclusion, the learning constructed through the authentic assessment dimensions was effective to foster students’ attitudes.belajar mahasiswa meliputi aspek student’s interest dan enjoyment pada Mata Kuliah Metode Spektroskopi Analisis (Analitik III). Subjek penelitian ini adalah 37 mahasiswa kimia yang memprogram Mata Kuliah Analitik III di FMIPA-UNESA. Penelitian ini dilakukan menggunakan desain studi kasus yang mana teknik pengambilan data dilakukan melalui observasi dan interview. Data yang diperoleh menunjukkan respon positif selama pembelajaran (pembelajaran yang dirancang menggunakan dimensi-dimensi penilaian otentik) pada mata kuliah ini. Mereka merasa tertarik (student’s interest) belajar pada topik yang mereka pelajari karena tiga alasan yaitu belajar teori melalui praktik, diskusi secara intensif dan aktifitas seperti seorang profesional. Kesenangan belajar (student’s enjoyment) timbul karena empat hal, antara lain adanya diskusi, tidak dipaksa memahami semua konsep pada satu kali pertemuan, adanya integrasi yang baik antara teori dan praktek dan belajar dalam kelompok. Dengan demikian, dapat disimpulkan bahwa penilaian otentik efektif untuk menimbulkan dan mendorong sikap belajar mahasiwa.